2020
DOI: 10.1002/cssc.201902848
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Conversion of Xylan into Furfural using Acidic Deep Eutectic Solvents with Dual Solvent and Catalyst Behavior

Abstract: An efficient process for the production of furfural from xylan by using acidic deep eutectic solvents (DESs), which act both as solvents and catalysts, is developed. DESs composed of cholinium chloride ([Ch]Cl) and malic acid or glycolic acid at different molar ratios, and the effects of water and γ‐valerolactone (GVL) contents, solid/liquid (S/L) ratio, and microwave heating are investigated. The best furfural yields are obtained with the DES [Ch]Cl:malic acid (1:3 molar ratio)+5 wt % water, under microwave h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 45 publications
1
53
1
Order By: Relevance
“…Few studies have reported the extraction and valorization of xylans using DES as solvent media [18,35,36] . For instance, a xylan pre‐extraction step from biomass was developed with the mild alkaline‐based [Ch]Cl : Urea aiming at preserving the xylan structure [35] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have reported the extraction and valorization of xylans using DES as solvent media [18,35,36] . For instance, a xylan pre‐extraction step from biomass was developed with the mild alkaline‐based [Ch]Cl : Urea aiming at preserving the xylan structure [35] .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a xylan pre‐extraction step from biomass was developed with the mild alkaline‐based [Ch]Cl : Urea aiming at preserving the xylan structure [35] . On another perspective, the use of acid‐based DES, such as [Ch]Cl:Oxalic acid and [Ch]Cl:Malic acid, allowed a favorable conversion of xylans into furfural [18] . Although some trends have been reported with acid‐based DES, the fate of hemicelluloses during [Ch]Cl/LA delignification media has not been explored.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they present similar "designer solvent" characteristics (Zhang et al, 2012) given the large variety of HBAs and HBDs that can be used and respective proportions. Over the last few years, the use of DES as greener alternatives to conventional solvents for lignocellulosic biomass processing has attracted increased attention, in areas spanning from delignification (Shen et al, 2019;Soares et al, 2017;Alvarez-Vasco et al, 2016) to high value compounds extraction (Gullón et al, 2019) and their conversion into added value products (Morais et al, 2020).…”
Section: Introductionmentioning
confidence: 99%